Human Rights Violations in Global Value Chains: A Locally Grounded Governance Framework - Rapior, Myriam C. (Journal of business ethics, 2026)
Social governance models of global value chains (GVCs) are criticized as being dominated by advanced economy multinational corporations (MNCs) and primarily focusing on civil society organizations (CSOs) from developed countries, marginalizing the local agency, knowledge, and needs of rightsholders at the producing end of the GVC. These traditional governance frameworks often reinforce corporate power by framing compliance as a linear, top-down mandate. We address these shortcomings in the literature by proposing a locally grounded governance framework that accounts for vulnerable rightsholders who are often sidelined or underrepresented. The study is based on an inductive qualitative analysis of 54 interviews with CSOs operating in rightsholders’ home countries, MNCs’ home countries, and globally. Our study contributes in two major ways. First, we develop a theoretical model that conceptualizes a shift from a static, meeting-minimum-legal-standards, compliance-driven model to an adaptive, locally grounded GVC governance framework that is genuinely collaborative and can evolve with local insights. Second, we theorize a shift from a linear top-down framework that reinforces corporate power to an iterative process in which the dynamics of conflict and collaboration interact and shape the outcomes of the governance model.